2019
DOI: 10.1063/1.5111588
|View full text |Cite
|
Sign up to set email alerts
|

Anneal mediated deep-level dynamics in GaInNAsSb dilute nitrides lattice-matched to GaAs

Abstract: This study focuses on the relationship among defects, annealing temperatures, and solar cell properties in the molecular beam epitaxy-grown GaInNAsSb solar cells. Samples with an n-i-p double heterostructure were annealed at various temperatures from 650 to 850 °C, and the dynamics of deep-level defects were analyzed. A significant improvement was obtained between 750 and 800 °C due to suppression of both the traps and the nonradiative recombination centers. They were distinguished using the DC bias dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
0
1
1
Order By: Relevance
“…RTP at 700°C and 750°C were conducted during 30 seconds on A and B samples. In contrast to a large part of literature reports [7,13,14], we found that RTP does not improve material properties. No change in dark current density was observed and PL signal was found to be higher for unannealed samples.…”
Section: B Motivation For Processing As-grown Cellscontrasting
confidence: 99%
“…RTP at 700°C and 750°C were conducted during 30 seconds on A and B samples. In contrast to a large part of literature reports [7,13,14], we found that RTP does not improve material properties. No change in dark current density was observed and PL signal was found to be higher for unannealed samples.…”
Section: B Motivation For Processing As-grown Cellscontrasting
confidence: 99%
“…The extension of the SCR can be calculated assuming that the dielectric permittivity of the dilute nitride layer is the same as GaAs and considering a built-in voltage of 0.5 V. The SCR width is estimated to range from 150 nm for sample C, to more than 420 nm for sample D. These depletion widths are very similar to results reported by Jackrel et al [37], but shorter than what is reported for BGCC lower than 5×10 14 cm -3 [38], [39].…”
Section: A Materials Characterizationsupporting
confidence: 82%
“…Соединения GaNAs, GaInNAs и GaInNAsSb за последние два десятилетия привлекают большое внимание исследователей из-за их уникальных свойств и потенциала применения в современных оптоэлектронных устройствах, особенно в высокоэффективных многопереходных солнечных элементах, инфракрасных лазерах и фотоприемниках. Основная задача таких исследований -объяснение влияния глубокоуровневых дефектов на производительность и параметры будущих устройств [5,6]. Несмотря на это, продвижение в направлении получения количественных результатов, относящихся к конкретным примесям или иным точечным дефектам, например, вакансиям, пока незначительно.…”
Section: Introductionunclassified